Odpowiedź :
[tex]a) \frac45+\frac1{10}=\frac8{10}+\frac1{10}=\frac9{10}\\b) \frac16+\frac23=\frac16+\frac46=\frac56\\c) \frac23+\frac15=\frac{10}{15}+\frac3{15}=\frac{13}{15}\\d) \frac47+\frac12=\frac{8}{14}+\frac7{14}=\frac{15}{14}=1\frac1{14}\\e) \frac89-\frac13=\frac89-\frac39=\frac59\\f) \frac3{10}-\frac15=\frac3{10}-\frac2{10}=\frac1{10}\\g) \frac45-\frac23=\frac{12}{15}-\frac{10}{15}=\frac2{15}\\h) \frac57-\frac14=\frac{20}{28}-\frac{7}{28}=\frac{13}{28}[/tex]
[tex]i)2\frac25+3\frac12=2\frac{4}{10}+3\frac5{10}=5\frac9{10}\\j) 4\frac37+2\frac23=4\frac{9}{21}+2\frac{14}{21}=6\frac{23}{21}=7\frac2{21}\\k) 2\frac38+1\frac16=2\frac{9}{24}+1\frac{4}{24}=3\frac{13}{24}\\l) 4\frac12+2\frac35=4\frac{5}{10}+2\frac6{10}=6\frac{11}{10}=7\frac1{10}[/tex]
[tex]m) 4\frac14-2\frac23=4\frac{3}{12}-2\frac{8}{12}=3\frac{15}{12}-2\frac8{12}=1\frac7{12}\\n) 5\frac19-1\frac56=5\frac{2}{18}-1\frac{15}{18}=4\frac{20}{18}-1\frac{15}{18}=3\frac5{18}\\o) 3\frac1{15}-1\frac1{10}=3\frac2{30}-1\frac{3}{30}=2\frac{32}{30}-1\frac3{30}=1\frac{29}{30}\\p) 5\frac5{13}-3\frac12=5\frac{10}{26}-3\frac{13}{26}=4\frac{36}{26}-3\frac{13}{26}=1\frac{20}{26}=1\frac{10}{13}[/tex]
a) [tex]\frac{4}{5} + \frac{1}{10} = \frac{8}{10} + \frac{1}{10} = \frac{9}{10}[/tex]
b) [tex]\frac{1}{6} + \frac{2}{3} = \frac{1}{6} + \frac{4}{6} = \frac{5}{6}[/tex]
c) [tex]\frac{2}{3} + \frac{1}{5} = \frac{10}{15} + \frac{3}{15} = \frac{13}{15}[/tex]
d) [tex]\frac{4}{7} + \frac{1}{2} = \frac{8}{14} + \frac{7}{14} = \frac{15}{14 } = 1\frac{1}{14}[/tex]
e) [tex]\frac{8}{9} - \frac{1}{3} = \frac{8}{9} - \frac{3}{9} = \frac{5}{9}[/tex]
f) [tex]\frac{3}{10} - \frac{1}{5} = \frac{3}{10} - \frac{2}{10} = \frac{1}{10}[/tex]
g) [tex]\frac{4}{5} - \frac{2}{3} = \frac{12}{15} - \frac{10}{15} = \frac{2}{15}[/tex]
h) [tex]\frac{5}{7} - \frac{1}{4} = \frac{20}{28} - \frac{7}{28} = \frac{13}{28}[/tex]
i) [tex]2\frac{2}{5} + 3\frac{1}{2} = 2\frac{4}{10} + 3\frac{5}{10} = 5\frac{9}{10}[/tex]
j) [tex]4\frac{3}{7} + 2\frac{2}{3} = 4\frac{9}{21} + 2\frac{14}{21} = 6\frac{23}{21} = 7\frac{2}{21}[/tex]
k) [tex]2\frac{3}{8} + 1\frac{1}{6} = 2\frac{9}{24} + 1\frac{4}{24} = 3\frac{13}{24}[/tex]
l) [tex]4\frac{1}{2} + 2\frac{3}{5} = 4\frac{5}{10} + 2\frac{6}{10} = 6\frac{11}{10} = 7\frac{1}{10}[/tex]
m) [tex]4\frac{1}{4} - 2\frac{2}{3} = \frac{17}{4} - \frac{8}{3} = \frac{51}{12} - \frac{32}{12} = \frac{19}{12} = 1\frac{7}{12}[/tex]
n) [tex]5\frac{1}{9} - 1\frac{5}{6} = \frac{46}{9} - \frac{11}{6} = \frac{59}{18} = 3\frac{5}{18}[/tex]
o) [tex]3\frac{1}{15} - 1\frac{1}{10} = \frac{46}{15} - \frac{11}{10} = \frac{92}{30} - \frac{33}{30} = \frac{59}{30} = 1\frac{29}{30}[/tex]
p) [tex]5\frac{5}{13} - 3\frac{1}{2} = \frac{70}{13} - \frac{7}{2} = \frac{140}{26} - \frac{91}{26} = \frac{49}{26} = 1\frac{23}{26}[/tex]